Developmental Predictors of Cognitive and Adaptive Outcomes in Genetic Subtypes of Autism Spectrum Disorder. Issue 10 (12th September 2020) - Arnett, Anne B.; Beighley, Jennifer S.; Kurtz‐Nelson, Evangeline C.; Hoekzema, Kendra; Wang, Tianyun; Bernier, Raphe A.; Eichler, Evan E.
Abstract : Approximately one‐fourth of autism spectrum disorder (ASD) cases are associated with a disruptive genetic variant. Many of these ASD genotypes have been described previously, and are characterized by unique constellations of medical, psychiatric, developmental, and behavioral features. Development of precision medicine care for affected individuals has been challenging due to the phenotypic heterogeneity that exists even within each genetic subtype. In the present study, we identify developmental milestones that predict cognitive and adaptive outcomes for five of the most common ASD genotypes. Sixty‐five youth with a known pathogenic variant involving ADNP, CHD8, DYRK1A, GRIN2B, or SCN2A genes participated in cognitive and adaptive testing. Exploratory linear regressions were used to identify developmental milestones that predicted cognitive and adaptive outcomes within each gene group. We hypothesized that the earliest and most predictive milestones would vary across gene groups, but would be consistent across outcomes within each genetic subtype. Within the ADNP group, age of walking predicted cognitive outcomes, while age of first words predicted adaptive behaviors. Age of phrases predicted adaptive functioning in the CHD8 group, but cognitive outcomes were not clearly associated with early developmental milestones. Verbal milestones were the strongest predictors of cognitive and adaptive outcomes for individuals with mutations to DYRK1A, GRIN2B, or SCN2A . These trends inform decisions about treatment planning and long‐term expectations for affected individuals, and they add to the growing body of research linking molecular genetic function to brain development and phenotypic outcomes. Lay Summary: Researchers have found many genetic causes of autism including mutations to ADNP, CHD8, DYRK1A, GRIN2B, and SCN2A genes. We found that each genetic cause had different early developmental milestones that explained the overall functioning of the children when they were older. Depending on the genetic cause, the age that a child first starts walking and/or talking may help to better understand and support a child's development who has a mutation to one of the above genes. Autism Res 2020, 13: 1659–1669. © 2020 International Society for Autism Research and Wiley Periodicals LLC